Associations of Antimicrobial-Resistant Gram-Negative Bloodstream Infections with Outcomes among Hospitalized Pediatric Patients in the United States - Spaulding, Alicen Burns; Watson, David; Dreyfus, Jill; Heaton, Phillip; Koutsari, Christina; Kharbanda, Anupam B. (Journal of Pediatric Infectious Diseases, 2021)
Objective The aim of this study was to assess the impact of pediatric antimicrobial-resistant gram-negative bloodstream infections (GNBSIs).Methods A retrospective cohort study (2009–2016) was conducted using the Premier Healthcare Database among pediatric admissions with GNBSIs at hospitals reporting microbiology data. Infections for neonates and nonneonates were classified as multidrug resistance (MDR), resistant to one or two antibiotic drug classes (1–2DR), or susceptible.Results Among 1,276 GNBSIs, 266 (20.8%) infections were 1–2DR and 23 (1.8%) MDR. Compared with susceptible GNBSIs, MDR nonneonates had higher mortality and higher costs, whereas 1–2DR neonates had longer stays and higher costs.Conclusions Antimicrobial-resistant GNBSIs were associated with worse outcomes among pediatric hospitalized patients.
Keywords: antimicrobial resistance; bloodstream infections; pediatric